Don't lose focus: critical repeat photography of CSU's campus - Oldberg, Katherine, author (Colorado State University. Libraries, 2017)
Repeat photography is an effective way to analyze the built and natural environments in terms of time and space. Not only does critical repeat photography allow for historical analysis, it also requires keeping meticulous records, which can be used in future replication of the photographs and future research. Employing critical repeat photography to examine CSU's architecture tells us about literal snapshots of CSU's history and how these spaces have changed over time. Critical repeat photography of Morgan Library, Lory Student Center, Clark, and Green Hall demonstrates CSU's shift away from its post-war architecture towards a more cohesive vernacular.

With the prolific construction and destruction on Colorado State University (CSU)'s campus, CSU's built environment has drastically changed since World War II (WWII). Many post-war buildings are on the chopping block or have undergone drastic renovations greatly altering the building's façade. Which buildings has CSU razed? Which buildings has CSU kept, but transformed to meet CSU's shift towards one specific architectural vernacular? In order to explore these questions, I took a series of photos based on historic photographs from the 1960s I found in CSU's digital repository. The buildings I chose for my research included Clark, Morgan Library, Lory Student Center, and Green Hall. Clark, Morgan, and Lory are all in the same focal point of campus, serving the administrative and academic needs of CSU's student body. Green Hall served the students as a dorm. I chose these buildings because of their construction period and their varied use, representing important buildings to CSU's campus community. Repeat photography requires meticulous documentation. The process consists of finding the location the historic photograph was taken, determining the exact angle of the camera, taking into account the season of the historic photograph vs time of year current photo taken, and keeping detailed field records including GPS coordinates for future recorders to replicate the photo. Once I found the exact location and replicated the photographs, I analyzed the images as side-by-side comparisons of the historic photo and current photo. This critical repeat photography project helps keep records of these buildings as well as communicate echoes of CSU's history. From examining the images, I discovered CSU changed and added onto the exteriors of Morgan and Lory, demolished most of Green Hall, and painted Clark from white to beige and red. CSU does not have a seamless campus architecture like the University of Colorado at Boulder (CU). CU is known for its buildings' unifying flagstone construction. CSU does not have this iconic architecture. Instead, CSU directly reflects society and the campus needs at specific periods in its history. By not maintaining one specific type of architecture or using the same building materials, CSU is a university of the people, or as Jim Hansen coined, "Democracy's College." CSU's renovations of Lory and Morgan and its destruction of Green all demonstrate how CSU is attempting to create a cohesive architecture. The materials used to manipulate the elevations all mesh with the new construction and ongoing construction on campus. CSU has razed many buildings like Green Hall to make room for new buildings or parking lots or has significantly altered the buildings in the past 10 years. CSU is trying to use its architecture to assert its relevance in the state college conversation, but is ultimately ignoring and erasing its post-war boom and its architectural significance in a chapter of Colorado’s history. Repeat photography can shed some light on the dialogue between CSU's architecture and its history.
219 - Katherine Ruth Ellen Oldberg
Keywords: architecture; repeat photography